POTENSI INTERAKSI ANTIDIABETIK ORAL PADA PASIEN RAWAT JALAN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Qarriy 'Aina Urfiyya; Ai Syah (Jurnal Farmasi Indonesia, 2025)
Indonesia is ranked fifth with the highest number of Diabetes Mellitus (DM) patients in theworld, with 19.5 million patients in 2021, and is estimated to be 28.6 million in 2045. DMpatients can experience comorbidities and complications, so they are at risk ofpolypharmacy and drug interactions. The average number of drugs for DM patients is 8.9drugs per day and 38.8% have the potential to experience interactions. The purpose of thisstudy was to determine the potential incidence of oral antidiabetic interactions in theprescription of type 2 DM patients. The study used an observational design.The sample wasa prescription for outpatient type 2 DM patients at PKU Muhammadiyah Yogyakarta in theperiod October 2021 - March 2022, totaling 112 prescription sheets. Data analysis used chisquare test on SPSS ver. 23 to see the relationship between the number of drugs andpotential interactions. Drug interaction evaluation was based on drugs.com,go.drugbank.com and Drug Interaction Facts by Tatro (2009). The study showed that thehighest comorbidity was hypertension (25%) and the highest use of oral antidiabetics wasmetformin (45.9%). Potential oral antidiabetic interactions were identified in 52prescriptions out of 112 prescription sheets, with the highest percentage being theinteraction of metformin with furosemide (16%). There was a significant associationbetween the number of drugs prescribed and the incidence of potential oral antidiabeticinteractions (p=0.000). Type 2 DM patients who receive polypharmacy have a greaterpotential for drug interactions.